Development of Learning Media Innovation for Android-Based Web Programming Courses - Muhammad Alam Nur Haris; Mustari S Lamada; Syamsurijal Syamsurijal (Center of Research and Innovation Strengthen LP2M UNM, 2023)
This study aims to develop a learning media for the Android-based web programming course and evaluate the validity, practicality, and effectiveness of the learning media. The Research & Development (R&D) method was used with the Analysis, Design, Development, Implementation, & Evaluation (ADDIE) model. The research subjects consisted of 39 students from the Computer Science and Informatics Education Program who took the web programming course in the odd semester of the 2022/2023 academic year. Data was collected through validation sheets, questionnaires, and test sheets. The results showed that the Android-based learning media product developed had high validity according to expert assessments, effective criteria that met high interpretation, and practicality based on the analysis of student responses to the learning media. Therefore, it can be concluded that the Android-based learning media for the web programming course is feasible to use with the categories of validity, practicality, and effectiveness in the learning process in the Computer Science and Informatics Education Program, Department of Computer Science and Informatics, Faculty of Engineering, Makassar State University, in the Web Programming course.